2019
DOI: 10.1002/jlb.3a0818-329rrr
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-type plasminogen activator neutralizes LPS but not protease-activated receptor-mediated inflammatory responses to plasmin

Abstract: Tissue‐type plasminogen activator (tPA) activates fibrinolysis and also suppresses innate immune system responses to LPS in bone marrow‐derived macrophages (BMDMs) and in vivo in mice. The objective of this study was to assess the activity of tPA as a regulator of macrophage physiology in the presence of plasmin. Enzymatically active and enzymatically inactive (EI) tPA appeared to comprehensively block the response to LPS in BMDMs, including expression of proinflammatory cytokines such as TNF‐α and IL‐1β and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 50 publications
(121 reference statements)
1
24
0
Order By: Relevance
“…The structure of LRP1 includes cysteine-rich complement-type repeats, EGF repeats, b-propeller domains, and transmembrane and cytoplasmic domains. Proteolytic cleavage of the ectodomain of LRP1 by a disintegrin and metalloproteinase 10 (ADAM10), ADAM17, membrane type1-MMP, and tPA releases free LRP1 that can serve as a decoy receptor trapping ligands (like plasmin, tPA, and MMPs) in the extracellular space [ 61 ].…”
Section: The Endocytosis Receptor Lrp1 Controls the Inflammatory Respmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure of LRP1 includes cysteine-rich complement-type repeats, EGF repeats, b-propeller domains, and transmembrane and cytoplasmic domains. Proteolytic cleavage of the ectodomain of LRP1 by a disintegrin and metalloproteinase 10 (ADAM10), ADAM17, membrane type1-MMP, and tPA releases free LRP1 that can serve as a decoy receptor trapping ligands (like plasmin, tPA, and MMPs) in the extracellular space [ 61 ].…”
Section: The Endocytosis Receptor Lrp1 Controls the Inflammatory Respmentioning
confidence: 99%
“…2 ) due to the unique function of LRP1 to link to other receptors like NMDA-R. Mantuano et al demonstrated that the pro-inflammatory cytokine profile of LRP1 deficient macrophages is reversed in TLR4 activated macrophages [ 71 ]. In the presence of LPS-stimulated TLR4, EI-tPA that cannot promote plasmin generation and a2-macroglobulin suppresses NFkB signaling and TNFa, IL-6, CCL2/3 production by binding to the NFkB suppressing NMDA-R [ 61 , 74 ].
Fig.
…”
Section: Tpa Receptors Modulates Tlr-mediated Cytokine Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of tPA as an LPS response modifier is not dependent on its protease activity and is replicated by enzymatically-inactive tPA (EI-tPA). Instead, the effects of tPA on BMDMs are mediated by the N-methyl-D-aspartate receptor (NMDA-R), which is best known for its function as a neuronal synapse protein but also expressed by macrophages [12, 13]. LDL Receptor-related Protein-1 (LRP1), a transmembrane receptor that binds tPA [1418], probably functions as an NMDA-R co-receptor, decreasing the concentration of tPA required to trigger NMDA-R-dependent cell-signaling and gene regulatory events [1720].…”
Section: Introductionmentioning
confidence: 99%
“…The fibrinolytic drug, tissue-type plasminogen activator (tPA), has been systemically administered to treat ARDS in COVID-19 and appeared to be effective in some patients [2][3][4]. Since tPA has been reported to show an antiinflammatory effect in addition to a fibrinolytic action, this potential of tPA would be helpful for improving the prognosis of COVID-19 patients [11,12].…”
mentioning
confidence: 99%